The The Ownership of Generative AI Outputs as Objects of Contract in Islamic Commercial Law: an Analysis of Milk Theory, Ma’qud ‘alaih, and Maqasid al-shariah - Rian Agung Nugraha; Neneng Nurhasanah; Panji Adam Agus Putra; Ferdian Franata (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
The rapid development of Generative Artificial Intelligence (AI) has created new forms of economic transactions in which AI-generated outputs possess significant economic value. This phenomenon raises important legal questions within Islamic commercial jurisprudence (fiqh muamalah), particularly regarding ownership (milk), the validity of AI outputs as contractual objects (ma'qud 'alaih), and their conformity with maqasid al-shariah. This study aims to examine the legal status of Generative AI outputs through the perspectives of ownership theory, contractual object requirements, and maqasid al-shariah. The research employs a qualitative normative approach using a library research design. Data were collected from classical fiqh literature, fatwas issued by Islamic institutions, contemporary Sharia standards, and academic publications on AI and the digital economy. The data were analyzed using content analysis and a comparative madhhab approach. The findings indicate that lawful and economically valuable AI-generated outputs may be classified as mal mutaqawwim. However, ownership is not automatically established by every user prompt, but depends on meaningful human creative contribution and clear contractual arrangements between users and AI developers. Furthermore, AI outputs fulfill the requirements of ma'qud 'alaih when they satisfy the criteria of lawful subject matter, deliverability, and sufficient specification. From the perspective of maqasid al-shariah, AI-output transactions are permissible provided they promote the protection of wealth, intellect, life, and religion while avoiding harm to individuals and society.